Project Management (PM) in project: Tools of success factor? - Hasnan, Norlena; Osman, Nor Hasni; Mohtar, Shahimi (UUM College of Business, 2008)
Success is the ultimate goal in any project.However, the notion of "project success" particularly in construction industry has still yet to receive a finite definition. Furthermore, the description should include the diverse interests of all stakeholders which is frequently, very difficult to compromise in the real project world.The project success is seen as highly associated with the project management performance.To have a successful project and remain competitive in the market clearly demands that construction companies able to manage their projects effectively. They should operate the projects according to the objectives and should understand what needs to be done in the future.This shows how importance the management of project in order to ensure the success of the project. However, many argued project management success is not necessarily the main prerequisites for project success. Some may just perceive project management as the tactical routines that need to be done in the project route.Hence, this paper aims to explore the project management concepts and its impact on project success from the theoretical point of view.This paper also outlines the important elements in project management that can be the core competencies to gear projects towards success.